Comparative efficacy of incretin drugs on glycemic control, body weight, and blood pressure in adults with overweight or obesity and with/without type 2 diabetes: a systematic review and network meta-analysis - Liu, Song; Hu, Jiaqiang; Zhao, Chen; Liu, Hang; He, Chunyang (Frontiers in Endocrinology, 2025)
BackgroundThe rapid development of multi-receptor drugs targeting glucagon-like peptide-1 receptor (GLP-1R) is driving significant advancements in the treatment of individuals with type 2 diabetes and obesity. This systematic review and network meta-analysis aims to compare the efficacy and safety of multi-receptor drugs in adults with overweight or obesity, with or without type 2 diabetes.MethodsA systematic search was conducted in PubMed, Cochrane, Web of Science, Embase, CNKI, and WanFang databases up to May 12, 2024. Randomized controlled trials (RCTs) with an intervention duration of at least 12 weeks were included. The population of interest consisted of individuals with overweight or obesity, with or without type 2 diabetes. Eligible studies compared multi-receptor drugs with placebo or other multi-receptor drugs. The primary outcomes were weight reduction, glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), blood pressure changes, and adverse events. Risk of bias was assessed using the version 2 of the Cochrane risk-of-bias tool (ROB2), and a random-effects network meta-analysis was performed using the frequentist approach. Confidence in effect estimates was evaluated using the Confidence In Network Meta-Analysis (CINeMA) framework.ResultsA total of 24 trials, involving 9165 participants, were included. Retatrutide (mean difference (MD): -11.91 kg, 95% CI: -19.00 to -4.82, P-score: 0.80, p: 0.0003) and Tirzepatide (MD: -12.78 kg, 95% CI: -16.10 to -9.46, P-score: 0.89, p < 0.0001) exhibited superior efficacy in reducing body weight, with all other agents except Mazdutide (MD: -5.31 kg, 95% CI: -9.78 to -0.84, P-score: 0.37, p: 0.0189) achieving reductions of over 8 kg. In patients with type 2 diabetes, all agents reduced HbA1c by over 1%, with Tirzepatide (MD: -1.87%, 95% CI: -2.15 to -1.59, P-score: 0.87, p < 0.0001) and Mazdutide (MD: -1.89%, 95% CI: -2.43 to -1.35, P-score: 0.88, p < 0.0001) showing the greatest effects on glycemic control. For blood pressure management, Tirzepatide significantly reduced systolic blood pressure (MD: -6.69 mmHg, 95% CI: -7.62 to -5.75, P-score: 0.84, p < 0.0001) and diastolic blood pressure (MD: -3.73 mmHg, 95% CI: -4.75 to -2.71, P-score: 0.92, p < 0.0001), with nearly all agents lowering systolic blood pressure by more than 5 mmHg. Non-diabetic participants showed more pronounced improvements in both weight and blood pressure. Safety analysis revealed that Tirzepatide had a favorable safety profile and all agents showed no significant impact on serious adverse events compared to placebo.ConclusionsMulti-receptor drugs demonstrated substantial therapeutic potential in weight management, glycemic control, and blood pressure regulation in adults with overweight or obesity, with or without diabetes, with a generally favorable safety profile.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024554005.